Competition and propagule density affect sexual and clonal propagation of a weed. (3rd April 2017) - Atwater, Daniel Z.; Kim, Wonjae; Tekiela, Daniel R.; Barney, Jacob N.
Abstract : Many introduced species are capable of both sexual and vegetative reproduction. Our understanding of the ecology of such species depends on the trade-offs between vegetative and sexual reproduction and the ecological conditions that favor both modes of reproduction and how those factors influence the population ecology of introduced species. Here, we studied the efficacy of propagation via both seeds and rhizomes in Johnsongrass, a widespread invasive grass whose success is due to its prolific production of shattering seeds and rhizomes, the latter of which are readily dispersed by anthropogenic and natural processes. In a common garden in Virginia, we varied the density of seeds and rhizomes and manipulated whether recruits experienced interspecific competition. Johnsongrass recruited from both seeds and rhizomes. We compared the efficacy of seeds and rhizomes on a per propagule basis and by standardizing them according to their total carbon content. Rhizomes were more efficient than seeds on a per propagule basis, but seeds propagated more efficiently than rhizomes on a per unit of carbon basis, establishing in nearly all plots and obtaining much greater biomass than rhizomes. We also found that rhizomes were subject to stronger negative density dependence than seeds and were more sensitive to site variation and competition. Our results suggest that, provided sufficient dispersal, a single Johnsongrass plant produces enough propagules to establish over more than a hectare, even at relatively low propagule densities. Proper understanding of both seed and vegetative propagation is crucial for understanding the ecology of this and other invasive species that utilize multiple reproductive modes.